2006
DOI: 10.1007/s11071-006-9076-2
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear stochastic analysis of subharmonic response of a shallow cable

Abstract: The paper deals with the subharmonic response of a shallow cable due to time variations of the chord length of the equilibrium suspension, caused by time varying support point motions. Initially, the capability of a simple nonlinear two-degree-of-freedom model for the prediction of chaotic and stochastic subharmonic response is demonstrated upon comparison with a more involved model based on a spatial finite difference discretization of the full nonlinear partial differential equations of the cable. Since the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…As seen, the non-dimensional chord elongation e(t) is exposing the system both to external and parametric excitation. Based on simulations with a full non-linear finite difference model, it was demonstrated by Zhou et al [12] that the indicated two degree-of-freedom model was adequate in predicting to a high degree of accuracy the qualitative, and even quantitative, dynamic responses and chaotic behavior of the cable as seen from the midpoint trajectories under stochastic excitation, as shown in Fig. 3, and from the Poincare-maps of the in-plane modal coordinate shown in Fig.…”
Section: Mechanical Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…As seen, the non-dimensional chord elongation e(t) is exposing the system both to external and parametric excitation. Based on simulations with a full non-linear finite difference model, it was demonstrated by Zhou et al [12] that the indicated two degree-of-freedom model was adequate in predicting to a high degree of accuracy the qualitative, and even quantitative, dynamic responses and chaotic behavior of the cable as seen from the midpoint trajectories under stochastic excitation, as shown in Fig. 3, and from the Poincare-maps of the in-plane modal coordinate shown in Fig.…”
Section: Mechanical Modelmentioning
confidence: 97%
“…A theory for determining the probability of occupying either of these modes of vibration was derived based on a continuous time two-state Markov chain model. The corresponding stochastic resonance of order 2:1 was investigated by Zhou et al [12] based on analytical solutions for the deterministic ordered response, and the subharmonic stochastic response was analyzed by Monte Carlo simulations. It was found that the stochastic variations of the chord elongation enhanced the tendency to chaotic response relative to the comparable harmonic excitation, and that the coupled mode of vibration only exists for bandwidths below a certain critical value.…”
Section: Introductionmentioning
confidence: 99%
“…option N2, (27), must be applied). From β 1 it can be seen that the resonant terms are [1,2], [1,4], [1,5], [1,9], [1,12] and [1,15] for mode 1 and [2, 1], [2,6], [2,7], [2,11], [2,18] and [2,19] for mode 2. Applying option N2 to these terms gives the transformed equations of motionü…”
Section: A Two-degree-of-freedom Oscillatormentioning
confidence: 99%
“…These expressions have come from terms [1,1] and [1,11] in β 1 for mode 1 (note that terms [1,6], [1,7], [1,18] and [1,19] also result in a response at 3Ω however the corresponding terms in n * u1 are zero) and terms [2,2], [2,4], [2,5], [2,9], [2,12] and [2,15] for mode 2. The resulting amplitudes of these sinusoidal responses are X 1,3Ω and X 2,Ω respectively, where to calculate X 2,Ω (54) is used.…”
Section: A Two-degree-of-freedom Oscillatormentioning
confidence: 99%
See 1 more Smart Citation